Kajian Pelaksanaan Campuran Beton K 300 Dengan Variasi Waktu Waktu Menggunakan Molen - Namarubessy, Mario Filliphi (aspal, 2024)
Mario Filiphi Namarubessy nim: 1316174051 "concrete studies conducted by K 300 with variations in time using mollen engines" guided by David D. M. Huwae, S.T., M.T. and Ir. Hendrie Tahya, M.T.. It is a mixture of Portland cement or other hydraulic cement, soft aggregate, rough aggregate, water for the filler. Concrete planning is sought for quality so that it is necessary to test quality quality that starts with concrete planning. In analyzing the method of executing a mixture of K 300 concrete using a mollen engine mixing device by mixing crude aggregates, fine aggregates, cement and water with the same composition and time, and yet different on the transmission of mixed time. Analyzing the conventional mixture of concrete using it Intervals during mixing with molen machines and sifting data generated from the process of working on objects in the ambon state polytech-lab and producing powerful effects on the K 300 concrete as the time interval avariations. The strong conventional concrete mixing of K 300 USES the mollen machine using a variety of powerful 3-day time intervals pressure on concrete = 13.8076 n /mm2 while for high-day time intervals on 7 days pressure on concrete on average = 14.8545 n /mm2 and execution of test materials in the laboratory for accurate results need to be done. Keywords: intervals of time, design mix, strong press.